Self-healing fluorine-free anti-fingerprint treatment agent based on dynamic covalent network, coating and preparation method and application thereof
Patent Information
- Application Number
- CN202610370655.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-25
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-03-25
AI Technical Summary
[0005]本发明的目的是提供一种基于动态共价键网络的自修复无氟防指纹处理剂、涂层及其制备方法和应用,解决了现有涂层的耐磨性差,使用寿命短的问题,本发明的自修复无氟防指纹处理剂能够有效赋予涂层表面优异的防指纹防污性能,能够适用于光热环境下,具备自修复功能,从而显著延长玻璃产品的使用寿命,提升其使用体验和耐久性
(1)本发明的自修复无氟防指纹处理剂,具有自修复功能,基于Diels-Alder动态共价键的可逆特性,涂层在受损后可通过加热或近红外光照射实现自修复,修复效率达90%以上;
Smart Images

Figure CN122326057B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of coating technology, specifically relating to a self-healing fluorine-free anti-fingerprint agent based on a dynamic covalent bond network, a coating, its preparation method, and its application. Background Technology
[0002] With the widespread use of touchscreen electronic devices, fingerprint contamination on screen surfaces has become an increasingly prominent problem. Traditional anti-fingerprint treatments often use fluorinated compounds to reduce the surface energy of materials, but fluorinated compounds often have issues such as bioaccumulation and environmental persistence, and regions such as the EU have successively implemented restrictions on their use.
[0003] Existing fluorine-free anti-fingerprint technologies mainly rely on organosilicon or hydrocarbons to construct low surface energy surfaces, but they suffer from insufficient durability and lack of self-healing capabilities. For example, Chinese patent CN107033761A discloses a water-based fluorine-free anti-fingerprint and anti-fouling polymer composite coating and its application method. This coating comprises the following components by mass percentage: 10-90% water-based silicone-containing acrylate polymer, 0-50% crosslinking component, 0-5% catalyst, 5-50% cosolvent, and 0-85% water. The water-based silicone-containing acrylate polymer is obtained by polymerizing vinyl monomers. The vinyl monomers include one or more of low surface energy monomers, crosslinkable monomers, water-based monomers, and monomers that adjust glass transition temperature and film hardness. The low surface energy monomers refer to silicone-containing vinyl compounds, the crosslinkable monomers refer to vinyl compounds with hydroxyl groups, the water-based monomers refer to vinyl compounds with hydrophilic groups, and the monomers that adjust glass transition temperature and film hardness refer to vinyl compounds with different glass transition temperatures. Although the coating has good fingerprint and stain resistance, transparency and durability, is suitable for a variety of substrates and is environmentally friendly, it has poor abrasion resistance and a short service life. Once the surface is damaged, the fingerprint resistance is permanently lost.
[0004] It should be noted that the information disclosed in the background section above is only used to enhance the understanding of the background of this disclosure, and therefore may include information that does not constitute prior art known to those skilled in the art. Summary of the Invention
[0005] The purpose of this invention is to provide a self-healing fluorine-free anti-fingerprint agent, coating, preparation method, and application based on a dynamic covalent bond network. This invention solves the problems of poor wear resistance and short service life of existing coatings. The self-healing fluorine-free anti-fingerprint agent of this invention can effectively endow the coating surface with excellent anti-fingerprint and anti-fouling properties. It is suitable for use in light and heat environments and has a self-healing function, thereby significantly extending the service life of glass products and improving their user experience and durability.
[0006] To achieve the above objectives, the present invention provides a self-healing, fluorine-free anti-fingerprint agent based on a dynamic covalent bond network, which comprises the following components by mass fraction: 22-30% dynamic covalent functionalized organosilicon polymer solution, 4-10% surface thiol-modified photothermal responsive nanomaterials, 4-6% dynamic crosslinking agent, 4-7% silane coupling agent, 1-2% temperature-responsive surface control agent, 0.2-0.4% catalyst and 44.6-64.8% solvent.
[0007] The solid content of the dynamically covalently functionalized organosilicon polymer solution is 40-50%, wherein the dynamically covalently functionalized organosilicon polymer is a prefunctionalized polymer obtained by cycloaddition of the furan ring in the polymer as shown in Formula I with a dynamic crosslinking agent to introduce the dynamic covalent bond characteristics into the polymer molecular chain.
[0008] Formula I In Formula I, x is 150–350, y is 20–70, z is 15–50, and w is 5–20; in the dynamically covalently functionalized organosilicon polymer, the side chain contains furan rings and hydroxyl groups, and the density of furan groups is 0.9–1.1 mmol / g, and the density of hydroxyl groups is 0.7–1.5 mmol / g; the surface-modified photothermal responsive nanomaterial uses thiol-modified Cu. 1.5 Mn 1.5 O4@SiO2 core-shell nanomaterials.
[0009] This invention relates to a self-healing, fluorine-free anti-fingerprint agent based on a dynamic covalent network. It employs a combination of a dynamic covalent network (skeleton), photothermal nanomaterials (driving force), and a gradient surface structure (functionality), specifically a dynamically covalently functionalized organosilicon polymer, surface-thiol-modified photothermal responsive nanomaterials, and a temperature-responsive surface control agent. The dynamically covalently functionalized organosilicon polymer provides mechanical properties and dynamic bond sites, forming a dynamic covalent network that serves as the film-forming matrix. The surface-thiol-modified photothermal responsive nanomaterials utilize thiol-modified Cu... 1.5 Mn 1.5 O4@SiO2 core-shell nanomaterials, this material uses Cu 1.5 Mn 1.5 O4 spinel forms the core layer, mesoporous SiO2 forms the shell, and Cu... 1.5 Mn 1.5The photothermal conversion efficiency of O4 spinel is ≥40%, while the mesoporous SiO2 shell effectively disperses the core spinel, preventing agglomeration. Simultaneously, surface thiol modification provides abundant active sites for surface modification. The bonding between thiols and dynamically covalently functionalized organosilicon polymers further enhances the interfacial adhesion between the nanomaterials and the matrix. Specifically, the surface-thiol modified photothermal responsive nanomaterials undergo thiol-ene click chemistry reactions with maleimide double bonds and vinylsiloxane (silane coupling agent) in the dynamic crosslinking agent, thereby covalently integrating and anchoring themselves within the three-dimensional network formed by the dynamically covalently functionalized organosilicon polymer and the dynamic crosslinking agent. In the final coating, the chemical composition and physical properties are not uniform from the interface between the coating and the substrate to the surface in contact with air. Instead, they exhibit a continuous, gradual gradient distribution, known as a gradient surface structure. This structure is achieved through the spontaneous directional migration and enrichment of temperature-responsive surface control agents (such as polyether-polysiloxane block copolymers) during the coating curing process. These agents contain temperature-responsive segments with a low critical solution temperature (LCST). Below the LCST, they are compatible with water or the polymer matrix; above the LCST, they dehydrate and shrink, becoming incompatible, thus "driving" conformational changes and migrations throughout the molecule. The low surface energy segments form a dense arrangement on the surface, significantly reducing the free energy of the coating surface. This is a key component that imparts excellent fingerprint resistance, liquid repellency, and easy cleaning properties to the coating.
[0010] In addition, the other components in the self-healing fluorine-free anti-fingerprint agent have the following functions: 1) Through photothermal conversion, after the coating is damaged, the broken covalent bonds at the damaged site can be rebonded by heating or near-infrared light irradiation. The dynamic crosslinking agent can further promote the recombination of dynamic covalent bonds, improve the self-healing efficiency, and thus achieve the self-healing of the coating; 2) The silane coupling agent has one end (triethoxysilane end) forming a Si-O-Si covalent bond network with the glass substrate and itself through hydrolysis and condensation, and the other end (vinyl) is incorporated into the polymer substrate through reaction. Chains can enhance the adhesion between the treatment agent and the substrate surface and the durability of the coating, ensuring that the coating is not easy to fall off; 3) The maleimide double bond in the bismaleimide crosslinking agent undergoes [4+2] cycloaddition with the furan ring on the polymer side chain. Vinyltrimethoxysilane begins to absorb trace amounts of water in the system, and its methoxy (-OCH3) undergoes hydrolysis to generate more reactive silanol (-Si-OH). Subsequently, silanols undergo dehydration condensation with each other or with the hydroxyl groups on the substrate / polymer to form strong Si-O-Si or Si-O-substrate covalent bonds.
[0011] The dynamically covalently functionalized organosilicon polymer used in this invention contains furan rings in its side chains, and the furan group density is 0.9~1.1 mmol / g. This density range ensures sufficient dynamic reaction sites on the polymer molecular chain while retaining hydroxyl groups for subsequent silane crosslinking. "Controlling furan group density" in this invention refers to adjusting the molar percentage of furan-functionalized monomers (such as furfuryl acrylate) in the total monomer feed to ensure that the number of molar furan groups per gram of solid in the final polymer is consistently within the range of 0.9~1.1 mmol, accurately reflecting and reproducibly controlling the concentration of dynamic crosslinking sites in the polymer network. "Retaining hydroxyl groups" refers to introducing hydroxyl-containing monomers (such as hydroxyethyl acrylate) through copolymerization and controlling their feed ratio to give the polymer a specific hydroxyl density. The hydroxyl density of the dynamically covalently functionalized organosilicon polymer is 0.7~1.5 mmol / g, and the hydroxyl density is controlled by the feed ratio of hydroxyethyl methacrylate in the comonomer. This density range ensures that the polymer provides sufficient reaction sites for the silane coupling agent, thereby achieving excellent adhesion and network strength, while avoiding the adverse effects of excessive hydroxyl groups on the hydrophobicity and chain mobility of the coating.
[0012] The dynamically covalently functionalized organosilicon polymer of this invention introduces dynamic covalent bond characteristics into the polymer molecular chain itself through the reaction of a dynamic crosslinking agent with the furan ring of the polymer side chain of Formula I, resulting in a prefunctionalized polymer. When formulating the treatment agent, bismaleimide needs to be added as a dynamic crosslinking agent. During the coating curing process, the added crosslinking agent will undergo a further Diels-Alder reaction with the remaining furan ring on the prefunctionalized polymer chain, thereby constructing a complete three-dimensional dynamic covalent network between the polymer chains.
[0013] Preferably, in Formula I, x is 190~200, y is 30~40, z is 25~35, and w is 5~15. More preferably, in Formula I, x is 192, y is 34, z is 30, and w is 10.
[0014] Preferably, the dynamic crosslinking agent is selected from bismaleimide crosslinking agents; or / and, the silane coupling agent is selected from vinyl-containing siloxanes; or / and, the temperature-responsive surface control agent is selected from temperature-responsive polysiloxanes; or / and, the catalyst is selected from blocked p-toluenesulfonate; or / and, the solvent is selected from isopropanol and propylene glycol methyl ether acetate.
[0015] Preferably, the bismaleimide crosslinking agent is selected from 1,6-bis(2-maleimide ethoxy)hexane or 1,6-bismaleimide hexane; or / and, the vinyl-containing siloxane is selected from vinyltrimethoxysilane; or / and, the temperature-responsive polysiloxane is selected from polyether-polysiloxane block copolymers, poly(N-isopropylacrylamide) modified polysiloxanes, or polyethylene oxide-polypropylene oxide block modified polysiloxanes; or / and, the catalyst is selected from pyridine-blocked p-toluenesulfonate; or / and, in the solvent, the mass ratio of isopropanol to propylene glycol methyl ether acetate is 1:(0.9~1).
[0016] The second objective of this invention is to provide a method for preparing the self-healing fluorine-free anti-fingerprint agent based on a dynamic covalent bond network, the method comprising the following steps: (S1) The surface-modified thiol photothermal responsive nanomaterials were mixed with isopropanol and pre-dispersed to obtain a uniform photothermal responsive nanomaterial dispersion; the dynamic covalent bond functionalized organosilicon polymer solution was diluted with propylene glycol methyl ether acetate to obtain a uniform furan polymer solution. (S2) The photothermal responsive nanomaterial dispersion is slowly added to the furan polymer solution to obtain a first mixture; (S3) Slowly add the silane coupling agent to the first mixture, and then add the dynamic crosslinking agent and the temperature-responsive surface control agent in sequence to obtain the second mixture; (S4) The mixture of catalyst and isopropanol is slowly added to the second mixture to obtain the third mixture; (S5) Isopropanol and propylene glycol methyl ether acetate are added to the third mixture to adjust the viscosity, and the mixture is aged under an inert atmosphere.
[0017] Preferably, in step (S1), the pre-dispersion is performed by ultrasonic dispersion at a power of 300~500W, with the temperature controlled at ≤30℃; or / and, in step (S1), propylene glycol methyl ether acetate is added to the dynamically covalently functionalized organosilicon polymer solution for dilution, and mechanical stirring is performed at a speed of 200~300 r / min to obtain a uniform furan polymer solution; or / and, in step (S2), the photothermal responsive nanomaterial dispersion is slowly added to the furan polymer solution, with the addition rate controlled at 1~2 mL / min, and the stirring speed is simultaneously increased to 500~700 r / min. After the addition is complete, stirring continues, and the temperature is maintained at 25±2℃ to obtain a first mixture; or / and, In step (S3), the silane coupling agent is slowly added to the first mixture at a speed of 500-700 r / min, and the addition time is controlled to be completed in 4-6 minutes; or / and, in step (S3), molten dynamic crosslinking agent is added, the system temperature is maintained at 60±2℃, the stirring speed is increased to 750-850 r / min, the addition time is 8-15 minutes, and then a temperature-responsive surface control agent is added, the speed is adjusted to 300-500 r / min, and the addition is completed within 3-5 minutes to obtain the second mixture; or / and, in step (S5), the aging treatment is carried out by reducing the stirring speed to 150-250 r / min, maintaining the temperature at 25±1℃, and using inert gas protection throughout the process.
[0018] Preferably, the preparation of the surface-modified photothermal responsive nanomaterial comprises: Cu 1.5 Mn 1.5 O4 spinel was dispersed in an aqueous ethanol solution, ammonia and tetraethyl orthosilicate were added, and the mixture was stirred at room temperature to obtain Cu. 1.5 Mn 1.5 O4@SiO2 core-shell nanoparticles; The Cu 1.5 Mn 1.5 O4@SiO2 core-shell nanoparticles were dispersed in toluene, and 3-mercaptopropyltriethoxysilane was added. The mixture was then refluxed to obtain a surface-modified photothermal responsive nanomaterial.
[0019] Preferably, the preparation of the dynamically covalently functionalized organosilicon polymer solution comprises: mixing methyl methacrylate, hydroxyethyl acrylate, furfuryl acrylate, vinyltriethoxysilane and an initiator evenly, adding propylene glycol methyl ether acetate, and carrying out a free radical copolymerization reaction at 70-80°C under inert gas protection to obtain a polymer with furan rings and silane groups in the side chains, then adding a dynamic crosslinking agent and reacting at 70-80°C to obtain the dynamically covalently functionalized organosilicon polymer solution.
[0020] More preferably, the initiator is selected from azobisisobutyronitrile.
[0021] More preferably, the molar ratio of methyl methacrylate, hydroxyethyl methacrylate, furfuryl acrylate, and vinyltriethoxysilane is (45~65):(8~12):(7~10):(1.5~3.0); or / and, the amount of the initiator is 0.8%~1.5% of the total mass of the four monomers; or / and, the ratio of the amount of propylene glycol methyl ether acetate to the total mass of the four monomers is (1.5~2.5):1; or / and, the molar ratio of the dynamic crosslinking agent to furfuryl acrylate is (7~10):6.
[0022] A third objective of this invention is to provide the application of the self-healing, fluorine-free anti-fingerprint agent based on a dynamic covalent bond network in preventing fingerprints and stains.
[0023] The fourth objective of this invention is to provide a coating of the self-healing fluorine-free anti-fingerprint agent based on a dynamic covalent network.
[0024] The fifth objective of this invention is to provide a method for preparing the coating, wherein the product to be treated is immersed in the self-healing fluorine-free anti-fingerprint treatment agent based on a dynamic covalent network, pulled up at a uniform speed to form a uniform wet film, pre-baked, and cured to form the coating.
[0025] Preferably, the uniform lifting speed is 1~3 mm / s; or / and the pre-baking temperature is 90~110℃; or / and the curing temperature is 130~150℃.
[0026] The sixth object of the present invention is to provide a glass product with the aforementioned coating.
[0027] Specifically, the self-healing fluorine-free anti-fingerprint treatment agent and coating described in this invention can be widely used in the surface protection treatment of various substrates, including but not limited to: screens and shells of consumer electronics products, display panels of automotive interiors, precision optical devices, surfaces of household appliances, and touch screens of medical devices, giving them durable anti-fingerprint, anti-fouling, and self-repairing functions.
[0028] The self-healing fluorine-free anti-fingerprint agent, coating, preparation method, and application based on dynamic covalent bond network of the present invention solve the problems of poor wear resistance and short service life of existing coatings, and have the following advantages: (1) The self-healing fluorine-free anti-fingerprint treatment agent of the present invention has a self-healing function. Based on the reversible characteristics of Diels-Alder dynamic covalent bonds, the coating can be self-healed by heating or near-infrared light irradiation after damage, with a repair efficiency of over 90%. (2) The self-healing fluorine-free anti-fingerprint treatment agent of the present invention is environmentally friendly, completely free of fluorine compounds, and meets environmental protection requirements; (3) The self-healing fluorine-free anti-fingerprint agent of the present invention has excellent durability. The dynamic covalent bond network endows the coating with good mechanical properties and durability. After 1000 friction tests, the water contact angle retention rate is greater than 95%. (4) The self-healing fluorine-free anti-fingerprint treatment agent of the present invention has intelligent repair and photothermal response nanomaterials that enable the coating to achieve point-to-point and time-based repair through near-infrared light, making it suitable for complex use environments. Attached Figure Description
[0029] Figure 1 The image shows the TEM test results of the surface-modified photothermal responsive nanomaterial prepared in Example 2 of this invention.
[0030] Figure 2 This is a cross-sectional SEM image of the self-healing fluorine-free anti-fingerprint coating prepared in Example 3 of the present invention. Detailed Implementation
[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0032] It should be noted that: Unless otherwise specified in the examples, conditions should be followed according to standard conditions or the manufacturer's recommendations. Instruments whose manufacturers are not specified are all commercially available products. Raw materials and reagents whose manufacturers are not specified are all commercially available goods or can be prepared using known methods.
[0033] In this invention, all features defined in the form of numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are used only for simplicity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0034] The features mentioned in this invention can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification, provided that there is no contradiction in the combination of these features. Each feature disclosed in the specification can be replaced by any alternative feature that provides the same, equivalent, or similar purpose. Therefore, unless otherwise specified, the disclosed features are merely general examples of equivalent or similar features.
[0035] In the description of this invention, it should be noted that the terms "comprising," "including," or any other variations thereof are intended to cover a non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element. Those skilled in the art will understand the specific meaning of the above terms in this invention according to the specific circumstances.
[0036] Example 1 A dynamically covalently functionalized organosilicon polymer, the preparation method of which includes: In a four-necked flask equipped with a stirrer, condenser, and thermometer, 64.47 g (0.64 mol) of methyl methacrylate, 14.95 g (0.11 mol) of hydroxyethyl methacrylate, 15.67 g (0.10 mol) of furfuryl acrylate, 4.91 g (0.03 mol) of vinyltrimethoxysilane, and 1.00 g (0.006 mol) of azobisisobutyronitrile (AIB) as initiator were weighed and mixed thoroughly. 200 g of propylene glycol methyl ether acetate was added as a solvent, and a free radical copolymerization reaction was carried out at 70–80 °C under nitrogen protection to obtain a polymer with furan rings and silane groups in the side chains, where x = 192, y = 34, z = 30, and w = 10. Then, 21.5 g (0.06 mol) of 1,6-bismaleimide hexane (purchased from Sigma-Aldrich) was added, and the reaction was carried out at 70 °C for 3 hours to conduct a Diels-Alder reaction.
[0037] After the reaction was completed, the temperature was lowered to below 40°C to obtain a solution of dynamically covalently functionalized organosilicon polymer with a solid content of about 45%.
[0038] Example 2 A photothermal responsive nanomaterial, the preparation method of which includes the following steps: (1) Cu 1.5 Mn 1.5 Synthesis of O4 spinel CuCl₂·2H₂O (1.7 g, 0.01 mol) and MnCl₂·4H₂O (2.0 g, 0.01 mol) were dissolved in 100 mL of ethylene glycol and ultrasonically dispersed until homogeneous. NaOH solution was added to adjust the pH to 12, and then the mixture was transferred to a 200 mL high-pressure reactor and reacted at 200 °C for 12 hours.
[0039] After the reaction was complete, the precipitate was collected by centrifugation, washed three times with ethanol and deionized water, and dried under vacuum at 60°C to obtain black Cu. 1.5 Mn 1.5 O4 spinel.
[0040] (2) Cu 1.5 Mn 1.5 Preparation of O4@SiO2 core-shell nanoparticles The above Cu 1.5 Mn 1.5 O4 spinel (0.5 g) was dispersed in a mixed solution of 200 mL ethanol and 50 mL deionized water and sonicated for 30 minutes. Then, 2 mL of 28 wt% ammonia and 2 mL of tetraethyl orthosilicate were added, and the mixture was stirred at room temperature for 24 hours.
[0041] After the reaction was complete, the product was collected by centrifugation and washed three times with ethanol to obtain Cu. 1.5 Mn 1.5 O4@SiO2 core-shell nanoparticles, with Cu 1.5 Mn 1.5 The core layer is O4 spinel, and the shell layer is mesoporous SiO2 with a thickness of 3~5nm.
[0042] (3) Surface modification The above core-shell nanoparticles were dispersed in 100 mL of toluene, and 1 mL of 3-mercaptopropyltriethoxysilane was added. The mixture was refluxed for 6 hours.
[0043] After the reaction was completed, the product was collected by centrifugation, washed three times with toluene, and dried to obtain surface-thiol-modified photothermal responsive nanomaterials. TEM test results are shown below. Figure 1 .
[0044] For the Cu prepared above 1.5 Mn 1.5 The photothermal properties of O4 spinel were tested as follows: The Cu obtained in Example 2 1.5 Mn 1.5 O4 spinel was prepared into an aqueous dispersion of 100 μg / mL. An 808 nm near-infrared laser (power density 1.0 W / cm²) was used for the analysis. 2 Irradiate the sample and record its temperature rise curve. Based on the standard photothermal conversion efficiency... η Calculation formula:
[0045] In the above formula, hS The heat dissipation coefficient of the system is obtained from the cooling curve; Δ T max This represents the maximum steady-state temperature rise. Q 0 represents background heat loss;P in The incident laser power; A 808 The absorbance of the sample at 808 nm is given.
[0046] Calculations show that the Cu prepared by this invention... 1.5 Mn 1.5 O 4尖晶石 The photothermal conversion efficiency is 42.5%, proving that it has excellent photothermal performance.
[0047] Example 3 A self-healing, fluorine-free anti-fingerprint treatment agent based on a dynamic covalent network comprises the following components by mass fraction (per 100g): 25% of a dynamically covalent functionalized organosilicon polymer solution prepared in Example 1, 8% of surface-modified photothermal responsive nanomaterials prepared in Example 2, 5% of a dynamic crosslinking agent (1,6-bismaleimide hexane), 5% of a silane coupling agent (vinyltriethoxysilane), 1.5% of a temperature-responsive surface control agent (polyether-polysiloxane block copolymer, i.e., polyether siloxane copolymer, Evonik TEGO® Glide 410), 0.3% of a catalyst, and 55.2% of a solvent (a mixture of isopropanol and propylene glycol methyl ether acetate).
[0048] The preparation method of the above-mentioned self-healing fluorine-free anti-fingerprint treatment agent includes: (1) Predispersion of photothermal responsive nanomaterials Accurately weigh the surface thiol-modified photothermal responsive nanomaterials prepared in Example 2, measure out isopropanol as the dispersion medium, slowly add 120g of isopropanol to the photothermal responsive nanomaterials, disperse for 15 minutes at 400W using an ultrasonic cell disruptor, cool in an ice-water bath throughout the process, and control the temperature to ≤30℃ to obtain a uniform photothermal responsive nanomaterial dispersion for later use. (2) Preparation of furan polymer solution Weigh the dynamically covalently functionalized organosilicon polymer solution prepared in Example 1, add 80g of propylene glycol methyl ether acetate (PMA) to dilute, turn on mechanical stirring, set the speed to 300r / min and stir continuously for 15 minutes until completely homogeneous to obtain a furan polymer solution. (3) Primary mixing The above photothermal responsive nanomaterial dispersion was slowly added to the above furan polymer solution. The addition rate of the dispersion was controlled at 1~2 mL / min, and the stirring speed was simultaneously increased to 600 r / min. After the addition was completed, stirring was continued for 30 minutes, and the temperature was maintained at 25±2℃ to obtain the first mixture. (4) Addition of functional additives Vinyltriethoxysilane was added to the first mixture at a slow speed of 600 rpm, with the addition time controlled to be 5 minutes. Stirring continued for 15 minutes after the addition was complete. Molten 1,6-bismaleimide hexane (dynamic crosslinking agent) was added to maintain the system temperature at 60±2℃. The stirring speed was increased to 800 rpm, with the addition time controlled to 10 minutes, and stirring continued for 20 minutes. Then, polyether-polysiloxane block copolymer (Evonik TEGO® Glide 410, a temperature-responsive surface control agent) was added, with the stirring speed adjusted to 400 rpm, completed within 3 minutes. Stirring continued for 15 minutes to obtain the second mixture.
[0049] (5) Catalyst addition A pyridine-blocked p-toluenesulfonate solution (concentration 30%) was mixed with 20g of isopropanol to obtain a catalyst mixture. The catalyst mixture was then slowly added to the second mixture to obtain a third mixture. The closed catalyst is stable at room temperature and decomposes to release p-toluenesulfonic acid during subsequent heating and curing (>90℃), thereby simultaneously and efficiently catalyzing the hydrolysis and condensation reaction of the siloxane network and the formation of Diels-Alder dynamic covalent bonds.
[0050] (6) Viscosity adjustment and aging Add the remaining 172g of propylene glycol methyl ether acetate and 120g of isopropanol solvent to the third mixture above to adjust the viscosity, and carry out aging treatment: reduce the stirring speed to 200r / min, age for 2 hours, maintain the temperature at 25±1℃, and provide nitrogen protection throughout the process.
[0051] The self-healing, fluorine-free anti-fingerprint agent based on a dynamic covalent network prepared in this embodiment was applied to the surface of a glass substrate, and its performance was tested, as follows: A clean glass substrate (100mm × 100mm × 1mm) was immersed in the treatment agent prepared in this embodiment and pulled up at a uniform speed of 2mm / s to form a uniform wet film. The coated substrate was pre-baked at 100°C for 5 minutes and then cured at 140°C for 20 minutes to form an anti-fingerprint coating with a dry film thickness of approximately 3μm. The optical, anti-fingerprint, mechanical, and self-healing properties, as well as chemical resistance, were tested, and the results are shown in Table 1.
[0052] Table 1 Performance test results of the treatment agent in this embodiment Note: Test standards include ASTM D1003 "Standard Test Method for Haze and Luminous Transmittance of Transparent Plastics"; ISO 27448 "Fine ceramics (advanced ceramics, advanced technical ceramics) - Test method for self-cleaning performance of semiconducting photocatalytic materials - Measurement of water contact angle"; "Standard Test Method for Film Hardness by Pencil Test"; and ASTM D4060 "Standard Test Method for Abrasion Resistance of Organic Coatings by the Taber Abraser". Steel Wool Resistance Test: A linear reciprocating friction tester was used with #0000 grade steel wool as the friction medium. Under a load of 500g, a stroke of 100mm, and 30 cycles / min, the coating surface was subjected to 5000 reciprocating friction cycles. After testing, the coating surface showed no visible scratches under the naked eye and a 10x magnifying glass, thus it was deemed "passed". Heat repair efficiency test: The dimensional change of a standard scratch before and after heat treatment at 80℃ / 10min was measured, and the result was calculated using the formula η=(1-W_ 愈合 / W_ 初始) ×100% calculation efficiency; Ethanol abrasion resistance test: The coating was repeatedly rubbed with an anhydrous ethanol-wetted cloth under a 500g load, with the standard being no damage to the coating and a water contact angle maintained at ≥100°. All tests were conducted in a standard environment of 23±2°C and 50±5%RH to ensure the accuracy and comparability of the evaluation results; the same applies to the following tables.
[0053] Example 4 A self-healing, fluorine-free anti-fingerprint treatment agent based on a dynamic covalent network comprises the following components by mass fraction: 22% dynamic covalent functionalized organosilicon polymer solution, 4% surface thiol-modified photothermal responsive nanomaterials, 4% dynamic crosslinking agent, 4% silane coupling agent, 1.0% surface control agent, 0.3% catalyst, and 64.7% solvent.
[0054] The preparation method of the self-healing fluorine-free anti-fingerprint agent in this embodiment is basically the same as that in Example 3, except that the amount of each component is different.
[0055] The self-healing fluorine-free anti-fingerprint agent prepared in this embodiment was applied to the surface of a glass substrate and its performance was tested. The method was the same as in Example 3, and the results are shown in Table 2.
[0056] Table 2 Performance test results of the treatment agent in this embodiment Example 5 A self-healing, fluorine-free anti-fingerprint agent based on a dynamic covalent network comprises the following components by mass fraction: 30% dynamic covalent functionalized organosilicon polymer solution, 10% surface thiol-modified photothermal responsive nanomaterials, 6% dynamic crosslinking agent, 7% silane coupling agent, 2.0% surface control agent, 0.3% catalyst, and 44.7% solvent.
[0057] The preparation method of the self-healing fluorine-free anti-fingerprint agent in this embodiment is basically the same as that in Example 3, except that the amount of each component is different.
[0058] The self-healing fluorine-free anti-fingerprint agent prepared in this embodiment was applied to the surface of a glass substrate and its performance was tested. The method was the same as in Example 3, and the results are shown in Table 3.
[0059] Table 3 Performance test results of the treatment agent in this embodiment Furthermore, to verify the performance of the self-healing fluorine-free anti-fingerprint agent of the present invention, the following comparative experiment was conducted: Comparative Example 1: A traditional fluorine-free anti-fingerprint treatment agent without dynamic covalent bonds, i.e., without the addition of a dynamically covalent bond-functionalized organosilicon polymer solution and a dynamic crosslinking agent during preparation, and with other conditions the same as in Example 3.
[0060] Comparative Example 2: Fluorine-containing anti-fingerprint treatment (commercially available product), purchased from Daikin Industries' OPTOOL DSX series.
[0061] Comparative Example 3: A dynamic anti-fingerprint treatment agent without photothermal responsive nanomaterials, i.e., without surface thiol modification of photothermal responsive nanomaterials during preparation, without steps (1) and (3), and with other conditions the same as in Example 3.
[0062] The treatment agent described above was applied to the surface of a glass substrate in accordance with Example 3 of the present invention, and its performance was tested in accordance with the experiment in Example 3. The results are shown in Table 4.
[0063] Table 4 Performance test results obtained from comparative experiments The embodiments of the present invention exhibit the best performance in terms of anti-fingerprint performance, self-healing function and overall durability. In particular, after introducing photothermal repair function, it achieves intelligent repair capabilities that traditional fluorine-free systems cannot achieve.
[0064] Although the transmittance of Comparative Example 1 (91.2%) is slightly higher than that of Example 3 of the present invention (89.5%), this is because it does not contain any nanoparticles or complex network structures that may affect light scattering. However, the traditional fluorine-free anti-fingerprint agent of Comparative Example 1 lacks the chemical basis (furan and maleimide) for constructing a dynamic reversible network. Therefore, it does not have any self-healing function and is significantly inferior in all aspects of performance, proving that the simple organosilicon system cannot meet the needs of high-end applications.
[0065] Comparative Example 2 (containing fluorine) showed the best initial fingerprint resistance, but it also lacked self-healing capabilities and posed environmental and safety risks.
[0066] Comparative Example 3 (without photothermal treatment) demonstrates the necessity of dynamic covalent bonds for self-healing. The thermal repair efficiency of Comparative Example 3 (without photothermal treatment) (91.5%) is very close to that of Example 3 (92.3%). However, due to the lack of photothermal conversion capability, Comparative Example 3 cannot achieve self-healing under near-infrared light irradiation, thus limiting its application flexibility. This invention employs surface-modified thiol-modified photothermal responsive nanomaterials. Thiol modification is not a simple surface treatment step, but rather achieves a "strong interfacial bond" between inorganic nanoparticles and an organic dynamic network, transforming nanoparticles from a physical additive into chemical cross-linking points of the network. This simultaneously and significantly improves the durability and stability of the coating. Moreover, the surface-modified thiol-modified photothermal responsive nanomaterials possess photothermal response characteristics, rapidly converting light energy into heat energy under near-infrared light irradiation, raising the local temperature of the coating to the reversible reaction temperature range of Diels-Alder dynamic covalent bonds, thereby triggering rapid self-healing of the coating. This expands the triggering mechanism of self-healing and enhances its value in practical applications.
[0067] In summary, this invention successfully achieves a balance between performance and environmental protection through the synergistic effect of dynamic covalent bonds and photothermal materials, providing a new technical route for fluorine-free anti-fingerprint technology.
[0068] Although the present invention has been described in detail through the preferred embodiments above, it should be understood that the above description should not be considered as a limitation of the present invention. Various modifications and substitutions to the present invention will be apparent to those skilled in the art after reading the above description. Therefore, the scope of protection of the present invention should be defined by the appended claims.
Claims
1. A self-healing, fluorine-free anti-fingerprint treatment agent based on a dynamic covalent bond network, characterized in that, This self-healing, fluorine-free anti-fingerprint treatment contains the following components by mass fraction: 22-30% dynamically covalently functionalized organosilicon polymer solution, 4-10% surface-modified photothermal responsive nanomaterials, 4-6% dynamic crosslinking agent, 4-7% silane coupling agent, 1-2% temperature-responsive surface control agent, 0.2-0.4% catalyst, and 44.6-64.8% solvent; The solid content of the dynamic covalent functionalized organosilicon polymer solution is 40-50%, wherein the dynamic covalent functionalized organosilicon polymer is a prefunctionalized polymer obtained by introducing dynamic covalent bond characteristics into the polymer molecular chain through cycloaddition of furan ring in polymer as shown in Formula I with dynamic crosslinking agent. Formula I In Formula I, x is 150 ~ 350, y is 20 ~ 70, z is 15 ~ 50, and w is 5 ~ 20; In the dynamically covalently functionalized organosilicon polymer, the side chain contains furan rings and hydroxyl groups, and the density of furan groups is 0.9~1.1 mmol / g, and the density of hydroxyl groups is 0.7~1.5 mmol / g; The surface-modified photothermal responsive nanomaterial uses thiol-modified Cu. 1.5 Mn 1.5 O4@SiO2 core-shell nanomaterials.
2. The self-healing fluorine-free anti-fingerprint treatment agent based on a dynamic covalent bond network according to claim 1, characterized in that, The dynamic crosslinking agent is selected from bismaleimide crosslinking agents; Or / and, the silane coupling agent is selected from vinyl-containing siloxanes; Or / and, the temperature-responsive surface control agent is selected from temperature-responsive polysiloxanes; Or / and, the catalyst is selected from blocked p-toluenesulfonate; Or / and, the solvent is selected from isopropanol and propylene glycol methyl ether acetate.
3. The self-healing fluorine-free anti-fingerprint treatment agent based on a dynamic covalent bond network according to claim 2, characterized in that, The bismaleimide crosslinking agent is selected from 1,6-bis(2-maleimide ethoxy)hexane or 1,6-bismaleimide hexane; Or / and, the vinyl-containing siloxane is selected from vinyltriethoxysilane; Or / and, the temperature-responsive polysiloxane is selected from polyether-polysiloxane block copolymers, poly(N-isopropylacrylamide) modified polysiloxanes, or polyethylene oxide-polypropylene oxide block modified polysiloxanes; Or / and, the catalyst is selected from pyridine-blocked p-toluenesulfonate; Or / and, in the solvent, the mass ratio of isopropanol to propylene glycol methyl ether acetate is 1:(0.9~1).
4. The preparation method of the self-healing fluorine-free anti-fingerprint agent based on a dynamic covalent bond network as described in any one of claims 1 to 3, characterized in that, The method includes the following steps: (S1) The surface-modified thiol photothermal responsive nanomaterials were mixed with isopropanol and pre-dispersed to obtain a uniform photothermal responsive nanomaterial dispersion; the dynamic covalent bond functionalized organosilicon polymer solution was diluted with propylene glycol methyl ether acetate to obtain a uniform furan polymer solution. (S2) The photothermal responsive nanomaterial dispersion is slowly added to the furan polymer solution to obtain a first mixture; (S3) Slowly add the silane coupling agent to the first mixture, and then add the dynamic crosslinking agent and the temperature-responsive surface control agent in sequence to obtain the second mixture; (S4) The mixture of catalyst and isopropanol is slowly added to the second mixture to obtain the third mixture; (S5) Isopropanol and propylene glycol methyl ether acetate are added to the third mixture to adjust the viscosity, and the mixture is aged under an inert atmosphere.
5. The preparation method according to claim 4, characterized in that, In step (S1), the pre-dispersion is performed by ultrasonic dispersion at a power of 300~500W, with the temperature controlled at ≤30℃; Or / and, in step (S1), propylene glycol methyl ether acetate is added to the dynamically covalently functionalized organosilicon polymer solution for dilution, and mechanically stirred at 200~300 r / min to obtain a uniform furan polymer solution; Or / and, in step (S2), the photothermal responsive nanomaterial dispersion is slowly added to the furan polymer solution, the addition rate of the dispersion is controlled at 1~2 mL / min, the stirring speed is simultaneously increased to 500~700 r / min, stirring continues after addition is completed, and the temperature is maintained at 25±2℃ to obtain the first mixture; Or / and, in step (S3), the silane coupling agent is slowly added to the first mixture at a rotation speed of 500~700 r / min, and the addition time is controlled to be completed in 4~6 minutes; Or / and, in step (S3), add molten dynamic crosslinking agent, maintain system temperature at 60±2℃, increase stirring speed to 750~850r / min, add material over 8~15 minutes, then add temperature-responsive surface control agent, adjust stirring speed to 300~500r / min, and add within 3~5 minutes to obtain the second mixture; Or / and, in step (S5), the aging process involves reducing the stirring speed to 150~250 r / min, maintaining the temperature at 25±1℃, and using inert gas protection throughout.
6. The preparation method according to claim 4, characterized in that, The preparation of the surface-modified thiol-modified photothermal responsive nanomaterials includes: Cu 1.5 Mn 1.5 O4 spinel was dispersed in an aqueous ethanol solution, ammonia and tetraethyl orthosilicate were added, and the mixture was stirred at room temperature to obtain Cu. 1.5 Mn 1.5 O4@SiO2 core-shell nanoparticles; The Cu 1.5 Mn 1.5 O4@SiO2 core-shell nanoparticles were dispersed in toluene, and 3-mercaptopropyltriethoxysilane was added. The mixture was then refluxed to obtain a surface-modified photothermal responsive nanomaterial. Or / and, the preparation of the dynamically covalently functionalized organosilicon polymer solution comprises: Methyl methacrylate, hydroxyethyl acrylate, furfuryl acrylate, vinyltriethoxysilane, and an initiator were mixed evenly, and propylene glycol methyl ether acetate was added. Under inert gas protection, a free radical copolymerization reaction was carried out at 70-80°C to obtain a polymer with furan rings and silane groups in the side chain. Then, a dynamic crosslinking agent was added, and the reaction was carried out at 70-80°C to obtain a solution of dynamically covalently functionalized organosilicon polymer.
7. The application of the self-healing fluorine-free anti-fingerprint agent based on dynamic covalent bond network as described in any one of claims 1 to 3 in the prevention of fingerprints and stains.
8. A coating containing a self-healing fluorine-free anti-fingerprint agent based on a dynamic covalent network as described in any one of claims 1 to 3.
9. The method for preparing the coating as described in claim 8, characterized in that, The product to be treated is immersed in the self-healing fluorine-free anti-fingerprint treatment agent based on a dynamic covalent bond network, and then pulled up at a uniform speed to form a uniform wet film. After pre-baking and curing, the coating is formed.
10. A glass product containing the coating as described in claim 8.
Citation Information
Patent Citations
Waterborne fluoride-free fingerprint-proof and antifouling polymer composite coating and usage method thereof
CN107033761A
High-temperature solar absorbing coating with spinel structure
CN112011777A
Method of Strengthening a Brittle Oxide Substrate with a Weatherable Coating
US20080199618A1